Development of Alternative Energy-Based Temperature and Heat Module of Wood Waste Charcoal for Science Literacy - Triyanti, Dwi Erni; Mayub, Afrizal; Nursa’adah, Euis (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The low science literacy of students, especially in understanding temperature and heat materials, is a challenge in learning physics in schools. This material is often delivered theoretically without being associated with real life, so students have difficulty understanding concepts in their entirety. This research aims to develop a physics learning module on alternative energy-based temperature and heat materials from charcoal from wood and onion wood waste to improve students' science literacy. The research uses a 4D development model that is limited to the Define, Design, and Develop stages. The Define stage includes curriculum analysis, identification of student learning difficulties, and exploration of local potential. The Design Stage produces a contextual module design based on science literacy. At the Develop stage, the modules are validated by experts with results: 90% content aspect, 86% linguistics, and 95% presentation, with an average of 90% indicating the